Preparation and application of ZnIn2S4 / amorphous MoO3-x nanodot Z system photocatalyst

By loading amorphous MoO3-x nanodots on ZnIn2S4 to form a composite catalyst, the problem of low hydrogen production efficiency of ZnIn2S4 photocatalyst is solved, and efficient and stable photocatalytic performance is achieved, and the process is simple and environmentally friendly.

CN119259083AActive Publication Date: 2025-01-07CHINA UNIV OF MINING & TECH

Patent Information

Application Number
CN202411421303.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-07
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The photocatalytic hydrogen production efficiency of existing ZnIn2S4 photocatalysts is low, and their performance needs to be improved through modification, especially how to effectively combine local surface plasmon resonance effects and heterojunctions to improve photocatalytic performance is a technical challenge.

Method used

Ultrasonic chemistry method was used to synthesize amorphous MoO3-x nanodots and load them on ZnIn2S4 by a one-pot hydrothermal method to form a ZnIn2S4/amorphous MoO3-x nanodot composite catalyst to improve its photocatalytic hydrogen production performance.

Benefits of technology

It significantly improves the performance and stability of photocatalytic hydrogen production, expands the light absorption range, improves the electron-hole separation efficiency, and is simple in preparation and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259083A_ABST
    Figure CN119259083A_ABST
Patent Text Reader

Abstract

The invention discloses preparation and application of a ZnIn2S4 / amorphous MoO3-x nanodot Z system photocatalyst, and relates to the field of photocatalysis. The method is simple to operate and environment-friendly, and the prepared ZnIn2S4 / amorphous MoO3-x nanodot catalyst is excellent and stable in hydrogen production performance. The preparation method comprises the following steps: synthesizing amorphous MoO < 3-x > nanodots by using an ultrasonic chemical method, and loading the MoO < 3-x > nanodots on ZIS by using a one-pot hydrothermal method to obtain the ZM catalyst. The method comprises the following steps: weighing a certain amount of a ZM catalyst, placing the ZM catalyst in a quartz photoreactor, adding a triethanolamine aqueous solution without dissolved oxygen, introducing argon, exhausting air, and sealing the reactor; putting the reactor into a magnetic stirrer for stirring, and maintaining the temperature of the reactor through a thermostatic bath; the electron-hole separation efficiency of the composite catalyst is improved, the composite efficiency is reduced, and meanwhile, the light absorption range is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photocatalysis, and in particular to a ZnIn2S4 / amorphous MoO 3-x Preparation and application of nanodot Z system photocatalysts. Background Art

[0002] The massive consumption and over-combustion of fossil fuels have led to an energy crisis, causing serious harm to the global environment and human health. Therefore, it is necessary to develop clean, renewable alternative energy sources. Hydrogen energy has the advantages of high energy density and environmental friendliness, and is considered to be one of the best alternatives to fossil fuels. Semiconductor-based photocatalytic technology can convert renewable solar energy into hydrogen energy in the process of water decomposition. Therefore, the efficient and green photocatalytic hydrogen production reaction (HER) has attracted widespread attention from many researchers. In 1972, Fujijima first discovered that TiO2 can decompose water to produce hydrogen under light, and researchers have conducted extensive research on TiO2. However, the band gap of TiO2 is 3.2eV, and it mainly responds to the ultraviolet region of sunlight. The utilization rate of solar energy is low, which seriously limits its practical application. Therefore, the development of solar photocatalysts is expected to maximize the utilization and conversion of solar energy in the field of water decomposition.

[0003] In addition, ZnIn2S4 has a suitable band structure and strong visible light response, and is considered to be a favorable candidate for photocatalytic hydrogen evolution. However, due to the limitation of the light response range and the rapid recombination of photoinduced electron-hole pairs, single-component ZnIn2S4 usually exhibits low photocatalytic H2 production efficiency. In order to improve the hydrogen evolution performance of ZnIn2S4, it is necessary to modify it. Among them, the localized surface plasmon resonance (LSPR) effect and the construction of heterojunctions have been shown to effectively increase the light absorption range and inhibit electron-hole recombination, respectively.

[0004] Noble metal-semiconductor hybrid plasma photocatalysts have attracted extensive attention due to their excellent light absorption ability and excellent photocatalytic performance. However, noble metal nanoparticles are difficult to apply on a large scale due to their high cost and easy decomposition under light. 3-x Peng et al. prepared 0D / 2D CdS / MoO by a simple co-precipitation method. 3-x Heterojunction, thanks to MoO 3-x The LSPR effect extends the light absorption to the near-infrared region. Hu et al. synthesized black phosphorus / MoO by direct ball milling. 3-x Photocatalyst, MoO 3-x The presence of 2-hydroxy-2-nitrogen (2-hydroxy-2-nitrogen) increases the photocatalytic hydrogen production rate by 40 times.

[0005] In addition, the heterostructure can effectively inhibit the recombination of electrons and holes and improve the photocatalytic activity. Fan et al. designed a Cu with Z-type heterojunction. 0.5 Cd 0.5 S / MoO 3-x Catalysts achieve efficient photocatalytic hydrogen evolution. These studies show that LSPR effect and heterojunction coupling are effective strategies to improve photocatalytic performance. Therefore, how to couple LSPR effect and heterojunction to produce hydrogen more efficiently has become a technical problem that needs to be solved urgently by technicians in this field. Summary of the invention

[0006] In view of the above problems, the present invention proposes a ZnIn2S4 / amorphous MoO 3-x The preparation and application of nanodot Z system photocatalysts are simple to operate and environmentally friendly. 3-x Nanodot catalysts have excellent and stable hydrogen production performance.

[0007] The technical solution of the present invention is: firstly, amorphous MoO is synthesized by ultrasonic chemical method. 3-x The MoO nanodots were then synthesized by a one-pot hydrothermal method. 3-x The nanodots were loaded onto ZIS to obtain the ZM catalyst.

[0008] The following steps are involved:

[0009] Step A1: Using ultrasonic chemical method to reduce molybdenum trioxide (MoO3) powder to obtain amorphous MoO 3-x Nanodots;

[0010] Step A2: MoO 3-x Nanodots are loaded onto zinc indium sulfide (ZnIn2S4) to obtain ZnIn2S4 / amorphous MoO 3-x Nanodots (ZM), i.e. ZM catalysts

[0011] In step A1, amorphous MoO is synthesized by sonochemical method. 3-x The steps of nanodot are as follows:

[0012] 2 g of MoO3 powder was added to a beaker containing 200 mL of ethanol and water (ethanol-water volume ratio of 1:1), and the dispersion was ultrasonically treated at room temperature for 6 h, and then centrifuged at 3000 rpm for 45 min to obtain a supernatant. Ascorbic acid was then dissolved in the supernatant (ascorbic acid: supernatant = 8 mg: 20 mL), and ultrasonicated for 5 h to obtain a sample named MoO 3-x Nanodots.

[0013] The steps for synthesizing ZIS using hydrothermal method alone are as follows:

[0014] 1mmol ZnCl2, 2mmol InCl3·4H2O and 8mmol thioacetamide were added to a beaker containing 50mL ultrapure water. After ultrasonic treatment for 30min and stirring for 30min, the suspension was transferred into a 100ml polytetrafluoroethylene reactor and stored at 160℃ for 12h. After natural cooling, the precipitate was collected by centrifugation and washed with ultrapure water and anhydrous ethanol 3 times each. The final sample was dried in a vacuum oven at 60℃ for 12h to obtain ZnIn2S4, which was recorded as ZIS.

[0015] The steps for synthesizing ZM by one-pot hydrothermal method in step A2 are as follows:

[0016] Different volumes (5, 7, 10, 13 ml) of MoO 3-x The nanodots were added to a beaker containing 1mmol ZnCl2, 2mmol InCl3·4H2O and 8mmol thioacetamide, ultrasonicated for 30min, stirred for 30min, and then poured into a 100ml polytetrafluoroethylene reactor and reacted at 160℃ for 12h. After natural cooling, the precipitate was collected by centrifugation and washed with ultrapure water and anhydrous ethanol for 3 times each; the final sample was dried in a vacuum oven at 60℃ for 12h to obtain ZnIn2S4 / MoO 3-x , denoted as ZMX, X is the added MoO 3-x The volume of the nanodot.

[0017] Its application method is:

[0018] First, a certain amount of ZM catalyst was weighed and placed in a quartz photoreactor, and then a triethanolamine (TEOA) aqueous solution without dissolved oxygen was added, and the reactor was sealed after argon was introduced to exhaust the air. The reactor was placed in a magnetic stirrer for stirring, and the reactor temperature was maintained by a thermostatic bath. A xenon lamp was turned on to irradiate the reactor, and samples were taken at regular intervals. The extracted gaseous products were injected into a gas chromatograph for analysis to evaluate the hydrogen production effect of the catalyst.

[0019] The following steps are involved:

[0020] Step B1, add 10 mL of triethanolamine (TEOA) into a measuring cylinder containing 90 mL of aqueous solution, stir evenly with a glass rod; then introduce argon gas into the measuring cylinder and keep it for 30 minutes to remove dissolved oxygen;

[0021] Step B2, weigh 30 mg of the catalyst and pour it into a quartz photoreactor of about 480 mL, and then pour the above solution into it after passing argon gas, and then pass argon gas into the reactor for 5 minutes to exhaust the air, and then seal the reactor;

[0022] Step B3, placing the reactor on a magnetic stirrer for stirring, and using a thermostatic bath to maintain the temperature of the photocatalytic system at 10°C;

[0023] Step B4, using a 300W xenon lamp with an AM1.5G filter as a simulated sunlight source to irradiate the reactor; after turning on the light, extract 1mL of gaseous product from the reactor every 30min and analyze it with a gas chromatograph;

[0024] The apparent quantum efficiency (AQE) is calculated according to the following formula:

[0025]

[0026] Among them, N e is the number of reaction electrons, N p is the number of incident photons, nH2 is the number of moles of hydrogen produced in 1 hour, N A is Avogadro's constant, h is Planck's constant, c is the speed of light, I is the intensity of the incident light, S is the corresponding area of ​​irradiation, t is the illumination time, and λ is the wavelength of the incident light.

[0027] The present invention adopts ultrasonic chemical method and hydrothermal method to prepare the catalyst. 3-x Nanodots and ZnIn2S4 were composited in a 160℃ hydrothermal environment. The specific surface area of ​​the composite catalyst was significantly improved compared with that of pure ZnIn2S4. 3-x The photocatalytic hydrogen production performance of the composite catalyst was greatly improved after the nanodots were modified with ZnIn2S4. 3-x The loading of nanodots introduces hot electrons, which improves the electron-hole separation efficiency of the composite catalyst, reduces the recombination efficiency, and expands the light absorption range. More importantly, the present invention adopts ultrasonic chemical method and hydrothermal method, which is simple, efficient and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 ZnIn2S4 / amorphous MoO 3-x Schematic diagram of the preparation process of nanodot composite catalyst;

[0029] Figure 2 For ZIS, MoO 3-x XRD patterns of nanodots and ZMX;

[0030] Figure 3 (a) SEM image of ZIS; (b) SEM image of ZM10;

[0031] Figure 4 is (a)MoO 3-x TEM image of nanodots; (b) TEM image of ZIS; (c) TEM image of ZM10;

[0032] Figure 5(a) ZIS, MoO 3-x (a) Hydrogen production rate diagram of nanodots and ZMX; (b) Cyclic stability diagram of ZM10; (c) Apparent quantum efficiency diagram of ZIS and ZM10;

[0033] Figure 6 ZnIn2S4 / amorphous MoO 3-x Diagram of the hydrogen production mechanism of nanodots. DETAILED DESCRIPTION

[0034] In order to clearly illustrate the technical features of this patent, this patent is elaborated in detail below through a specific implementation method and in combination with its accompanying drawings.

[0035] The preparation of ZMX, the specific steps are as follows:

[0036] MoO 3-x Preparation of nanodots: 2 g of MoO3 powder was added to a beaker containing 200 mL of ethanol and water (ethanol-water volume ratio of 1:1). The dispersion was ultrasonically treated at room temperature for 6 h, and then centrifuged at 3000 rpm for 45 min to obtain a supernatant. Ascorbic acid was then dissolved in the supernatant (ascorbic acid: supernatant = 8 mg: 20 mL), and the sample was ultrasonically treated for 5 h, and then stored in a refrigerator at 4°C.

[0037] Preparation of pure ZIS: 1mmol ZnCl2, 2mmol InCl3·4H2O and 8mmol thioacetamide were added to a beaker containing 50mL ultrapure water. After ultrasonic treatment for 30min and stirring for 30min, the suspension was transferred into a 100ml polytetrafluoroethylene reactor and stored at 160℃ for 12h. After natural cooling, the precipitate was collected by centrifugation and washed with ultrapure water and anhydrous ethanol 3 times each. The final sample was dried in a vacuum oven at 60℃ for 12h to obtain ZnIn2S4, which was ground to obtain powder.

[0038] One-pot hydrothermal method was used to prepare ZMX: different volumes (5, 7, 10, 13 ml) of MoO 3-x The nanodots were added to a beaker containing 1mmol ZnCl2, 2mmol InCl3·4H2O and 8mmol thioacetamide, ultrasonicated for 30min, stirred for 30min, and then poured into a 100ml polytetrafluoroethylene reactor and reacted at 160℃ for 12h. After natural cooling, the precipitate was collected by centrifugation and washed with ultrapure water and anhydrous ethanol three times each. The final sample was dried in a vacuum oven at 60℃ for 12h to obtain ZnIn2S4 / MoO 3-x , denoted as ZMX (X is the added MoO 3-x The volume of the nanodots).

[0039] Figure 1The preparation process of the ZM catalyst is clearly described. Figure 2 XRD showed that MoO 3-x Amorphous properties of nanodots. Figure 3 The SEM images describe the morphological characteristics of ZIS and ZM10. Figure 4 TEM further describes the MoO 3-x The amorphous nature of nanodots, Figure 4 c shows that MoO 3-x Successfully loaded onto the ZIS.

[0040] The specific implementation process of ZMX photocatalytic hydrogen production is:

[0041] Add 10mL of triethanolamine (TEOA) to a measuring cylinder containing 90ml of aqueous solution, stir evenly with a glass rod; pass argon into the measuring cylinder for 30min to remove dissolved oxygen. Weigh 30mg of catalyst into a quartz photoreactor of about 480mL, and pour the above solution that has been passed with argon into it, pass argon into the reactor for 5min to exhaust all the air, and then seal the reactor. Place the reactor on a magnetic stirrer for stirring, and use a thermostatic bath to maintain the temperature of the photocatalytic system at 10℃, then use a 300w xenon lamp with an AM1.5G filter as a simulated sunlight source to irradiate the reactor. After turning on the light, extract 1mL of gaseous product from the reactor every 30min and analyze it with a gas chromatograph.

[0042] The hydrogen production rate of the catalyst within 3 hours is as follows Figure 5 a. The hydrogen production rate of ZIS is 1.34mmol·g-1·h-1, and MoO 3-x No hydrogen can be produced. With MoO 3-x With the introduction of ZM, the hydrogen production rate gradually increased; when 10 ml MoO 3-x When nanodots are added, the hydrogen production rate of ZM10 is the highest, which is 11.08mmol·g-1·h-1. Figure 5 b It can be seen that ZM10 still maintains good hydrogen production performance after five cycle experiments, indicating that the catalyst has strong chemical stability and good industrial potential.

[0043] The specific implementation process of the apparent quantum efficiency of ZIS and ZM10 is:

[0044] Add 10mL of triethanolamine (TEOA) to a measuring cylinder containing 90ml of aqueous solution, stir evenly with a glass rod; pass argon into the measuring cylinder for 30min to remove dissolved oxygen. Weigh 30mg of catalyst into a quartz photoreactor of about 480mL, and pour the above solution into it, pass argon into the reactor for 5min to exhaust all the air, and then seal the reactor. Place the reactor on a magnetic stirrer and stir, and use a thermostat to maintain the temperature of the photocatalytic system at 10℃, then irradiate the reactor with a 300w xenon lamp with bandpass filters of different wavelengths (350, 380, 420nm). After turning on the light for 1h, extract 1mL of gaseous product from the reactor and analyze it with a gas chromatograph.

[0045] Apparent quantum efficiency results Figure 5 As shown in c, the apparent quantum efficiency of ZM10 at 350, 380, and 420 nm is higher than that of ZIS. This result further illustrates that the MoO 3-x The introduction of nanodots onto ZIS can significantly improve the hydrogen production performance.

[0046] There are many specific implementation ways of the present invention. The above is only the preferred implementation mode of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements can be made without departing from the principle of the present invention. These improvements should also be regarded as the protection scope of the present invention.

Claims

1. A ZnIn2S4 / amorphous MoO 3-x The method for preparing a nanodot Z system photocatalyst is characterized in that: The following steps are involved: Step A1: Using sonicochemical method to reduce molybdenum trioxide powder to obtain amorphous MoO 3-x Nanodots; Step A2: MoO 3-x Nanodots are loaded onto zinc indium sulfide to obtain ZnIn2S4 / amorphous MoO 3-x Nanodots, i.e. ZM catalysts.

2. A ZnIn2S4 / amorphous MoO according to claim 1 3-x The method for preparing a nanodot Z system photocatalyst is characterized in that: In step A1, amorphous MoO is synthesized by sonochemical method. 3-x The steps of nanodot are as follows: MoO3 powder was added to a beaker containing ethanol and water, and the dispersion was ultrasonically treated at room temperature for 6 h, and then centrifuged at 3000 rpm for 45 min to obtain a supernatant. Ascorbic acid was then dissolved in the supernatant and ultrasonicated for 5 h to obtain a sample named MoO 3-x Nanodots; The steps for synthesizing ZM by one-pot hydrothermal method in step A2 are as follows: Different volumes of MoO 3-x The nanodots were added to a beaker containing 1mmol ZnCl2, 2mmol InCl3·4H2O and 8mmol thioacetamide, ultrasonicated for 30min, stirred for 30min, and then poured into a 100ml polytetrafluoroethylene reactor and reacted at 160℃ for 12h. After natural cooling, the precipitate was collected by centrifugation and washed with ultrapure water and anhydrous ethanol for 3 times each; the final sample was dried in a vacuum oven at 60℃ for 12h to obtain ZnIn2S4 / MoO 3-x , denoted as ZMX, X is the added MoO 3-x The volume of the nanodot.

3. A ZnIn2S4 / amorphous MoO according to claim 2 3-x The method for preparing a nanodot Z system photocatalyst is characterized in that: The mass of MoO3 in step A1: the volume of ethanol and water = 2g: 200mL; The volume ratio of ethanol to water is 1:1; Mass of ascorbic acid: volume of supernatant = 8 mg: 20 mL.

4. A ZnIn2S4 / amorphous MoO according to claim 2 3-x The method for preparing a nanodot Z system photocatalyst is characterized in that: Step A2 MoO 3-x The volume of the nanodots was 5, 7, 10, or 13 ml; The molar ratio of ZnCl2, InCl3·4H2O and thioacetamide is 1:2:

8.

5. A ZnIn2S4 / amorphous MoO prepared by the method of claim 1 3-x The application method of the nanodot Z system photocatalyst is characterized by: The following steps are involved: Step B1, add 10 mL of triethanolamine into a measuring cylinder containing 90 mL of aqueous solution, stir evenly with a glass rod; then introduce argon gas into the measuring cylinder and keep it for 30 minutes to remove dissolved oxygen; Step B2, weigh 30 mg of the catalyst and pour it into a quartz photoreactor of about 480 mL, and then pour the above solution into it after passing argon gas, and then pass argon gas into the reactor for 5 minutes to exhaust the air, and then seal the reactor; Step B3, placing the reactor on a magnetic stirrer for stirring, and using a thermostatic bath to maintain the temperature of the photocatalytic system at 10°C; Step B4, using a 300W xenon lamp with an AM1.5G filter as a simulated sunlight source to irradiate the reactor; after turning on the light, extract 1mL of gaseous product from the reactor every 30min and analyze it with a gas chromatograph; The apparent quantum efficiency (AQE) is calculated according to the following formula: Among them, N e is the number of reaction electrons, N p is the number of incident photons, nH2 is the number of moles of hydrogen produced in 1 hour, N A is Avogadro's constant, h is Planck's constant, c is the speed of light, I is the intensity of the incident light, S is the corresponding area of ​​irradiation, t is the illumination time, and λ is the wavelength of the incident light.

6. A ZnIn2S4 / amorphous MoO according to claim 5 3-x The application method of the nanodot Z system photocatalyst is characterized by: In step B1, the volume ratio of triethanolamine to water is 1:9; The mass of catalyst added in step B2: the volume of solution = 30 mg: 100 ml.

Citation Information

Patent Citations

  • Mo-doped MoO3@ZnIn2S4 Z system photocatalyst as well as preparation method and application thereof

    CN112495401A

  • Preparation method of MoS2 quantum dot doped ZnIn2S4 composite photocatalyst and application thereof

    CN113019400A

  • Preparation and application of two-dimensional ZnIn2S4 nanosheet modified WO3 flaky structure photocatalyst

    CN115837280A

  • MoO3-x / Cu0. 5Cd0. 5S composite photocatalyst as well as preparation method and application thereof

    CN115920929A

  • Non-noble metal plasma core-shell heterojunction material and preparation method and application thereof

    CN118287103A

Cited By

  • Few-layer amorphous MoO3-x nanosheet and preparation method thereof

    CN119976965A

  • A few-layer amorphous MoO 3-x Nanosheets and their preparation methods

    CN119976965B